2011
DOI: 10.1109/tsp.2010.2086449
|View full text |Cite
|
Sign up to set email alerts
|

Queue-Aware Distributive Resource Control for Delay-Sensitive Two-Hop MIMO Cooperative Systems

Abstract: In this paper, we consider a queue-aware distributive resource control algorithm for two-hop MIMO cooperative systems. We shall illustrate that relay buffering is an effective way to reduce the intrinsic half-duplex penalty in cooperative systems. The complex interactions of the queues at the source node and the relays are modeled as an average-cost infinite horizon Markov Decision Process (MDP). The traditional approach solving this MDP problem involves centralized control with huge complexity. To obtain a di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, it is difficult to apply MDP-based policies to large systems due to "curse of dimensionality." Wang et al [11] considered queue-based cooperative relaying by approximately solving MDP using a stochastic learning approach. The authors proposed a distributed online algorithm which is shown to be asymptotically optimal under the heavy-traffic limit.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to apply MDP-based policies to large systems due to "curse of dimensionality." Wang et al [11] considered queue-based cooperative relaying by approximately solving MDP using a stochastic learning approach. The authors proposed a distributed online algorithm which is shown to be asymptotically optimal under the heavy-traffic limit.…”
Section: Related Workmentioning
confidence: 99%
“…A related technique of utilizing multiple relays over timevarying channels, called cooperative relaying or opportunistic relaying, has been studied extensively [8][9][10][11][12][13]. Meanwhile, our model is applicable to the uplink transmission for cellular networks as well.…”
Section: Introductionmentioning
confidence: 99%
“…OLSP refers to the Optimal Link Selection Policy for a two-hop system with an infinite relay buffer in [9,Theorem 2]. NOP refers to the NearOptimal Policy obtained based on approximate value iteration using aggregation [20,Chapter 6.3], which is similar to the approximate MDP technique used in [21] and [22]. Note that, OLSP depends on the CSI only, while the other four baseline schemes depend on both of the CSI and QSI.…”
Section: B Throughput Performancementioning
confidence: 99%
“…Generally, there exist only numerical solutions, which do not typically offer many design insights and are usually impractical for implementation due to the curse of dimensionality [20]. For example, in [21], [22], the authors consider delay-aware control problems for two-hop relaying systems with multiple relay nodes and propose suboptimal distributed numerical algorithms using approximate Markov Decision Process (MDP) and stochastic learning [20]. However, the obtained numerical algorithms may still be too complex for practical systems and do not offer many design insights.…”
Section: Introductionmentioning
confidence: 99%
“…Often, even the basic structural properties of the delay optimal control policy are not known. While dynamic programming represents a systematic approach for delay optimal control, there generally exist only numerical solutions [1]- [5]. These solutions do not typically offer many design insights and are usually impractical for implementation in large-scale multi-hop networks, due to the curse of dimensionality [6].…”
Section: Introductionmentioning
confidence: 99%